2007
DOI: 10.1016/j.jadohealth.2007.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Self-Control Constructs Related to Measures of Dietary Intake and Physical Activity in Adolescents

Abstract: Purpose-To test self-regulation concepts in relation to dietary intake and physical activity patterns in adolescence, which we predicted to be influenced by components of a self-control model.Methods-A survey was conducted with a multiethnic sample of 9th grade public school students in a metropolitan area (N = 539). Confirmatory analysis tested the measurement structure of selfcontrol. Structural equation modeling tested the association of self-control constructs with measures of fruit and vegetable intake, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
100
1
10

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(123 citation statements)
references
References 36 publications
12
100
1
10
Order By: Relevance
“…Only very few observational studies have assessed the relationship between ER and obesity in children. Therefore, related factors such as executive function and self-control, which include similar aspects of ER, have also been included in the overview shown in Table 2 (51,52, [65][66][67][68][69][70][71] . Although the evidence is modest, better ER-related skills were associated with a healthier diet (more fruit/vegetables and less snack food, although not all studies reported significant findings), higher physical activity and, in some cases, a healthier weight status.…”
Section: A New Model For the Role Of Emotion Regulation In Obesity Dementioning
confidence: 99%
“…Only very few observational studies have assessed the relationship between ER and obesity in children. Therefore, related factors such as executive function and self-control, which include similar aspects of ER, have also been included in the overview shown in Table 2 (51,52, [65][66][67][68][69][70][71] . Although the evidence is modest, better ER-related skills were associated with a healthier diet (more fruit/vegetables and less snack food, although not all studies reported significant findings), higher physical activity and, in some cases, a healthier weight status.…”
Section: A New Model For the Role Of Emotion Regulation In Obesity Dementioning
confidence: 99%
“…In contrast, higher self-control has been linked to greater dietary health in adolescents. 109,110 Greater capacity to delay gratification is associated with lower levels of overweight and a slower rate of weight gain in childhood, [111][112][113] and better self-regulation skills at the age of 2 years predicted lower BMI and lower risk of obesity by the age of 5 years. 114 The literature on executive function provides a neuropsychological perspective on self-regulation.…”
Section: Links Between Restraint and General Self-regulatory Capacitymentioning
confidence: 99%
“…In general, good self-control has been associated with adaptive functioning, such as decreased externalizing symptoms, healthy dietary intake, increased physical activity, increased academic competence, more positive life events, decreased substance use, and fewer substance use-related problems (Wills et al, 2006(Wills et al, , 2007a(Wills et al, , 2007b. Furthermore, it attenuates the relationship between stressful life events and substance use (Wills et al, 2008).…”
Section: S Elf-regulation Of Behavior Is Central To Understanding Alcmentioning
confidence: 99%
“…Furthermore, it attenuates the relationship between stressful life events and substance use (Wills et al, 2008). In contrast, poor control has been associated with involvement in deviant peer groups, negative life events, increased internalizing and externalizing symptoms, poor dietary intake, a sedentary lifestyle, friends who use substances, adolescent substance use, and substance use problems (Wills et al, 2006(Wills et al, , 2007a(Wills et al, , 2007b. Thus, examining the relationship between these constructs and problematic alcohol use is important.…”
Section: S Elf-regulation Of Behavior Is Central To Understanding Alcmentioning
confidence: 99%